Kualitas Limbah Cair di Rumah Sakit Umum Daerah Kota Makassar Sulawesi Selatan - N, Amina Ramadana; J, Kartini (Barongko: Jurnal Ilmu Kesehatan, 2024)
In human life, water is an absolute necessity. Water is one of the most important necessities of life. Water is included in renewable natural resources, because it is continuously restored through the ongoing hydraulic cycle. The purpose of this study was to determine the description of the quality of liquid waste in Makassar Regional General Hospital. The research used was observational with a descriptive approach, namely to determine the study of the quality of liquid waste in Makassar Regional General Hospital. The TEMPERATURE parameter that the Makassar Regional General Hospital wastewater measurements based on the TEMPERATURE parameter in the morning and evening meet the requirements of 30ºC, this research is in accordance with research conducted by G. Nugroho Susanto, et al, 2008 On temperature measurements after further testing with the Smallest Real Difference (BNT) α = 0.05 there is no significant difference between one treatment and another treatment (Figure 4). The mean temperature of all treatments did not exceed the maximum limit of liquid waste quality standards for hospital activities, which is 30oC.